Intravoxel Incoherent Motion Imaging on Sacroiliitis in Patients With Axial Spondyloarthritis: Correlation With Perfusion Characteristics Based on Dynamic Contrast-Enhanced Magnetic Resonance Imaging - Guo, Chang; Zheng, Kai; Ye, Qiang; Lu, Zixiao; Xie, Zhuoyao; Li, Xin; Zhao, Yinghua (Frontiers in Medicine, 2022)
Background To prospectively explore the relationship between intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) and dynamic contrast-enhanced MRI (DCE-MRI) parameters of sacroiliitis in patients with axial spondyloarthritis (axSpA). Methods Patients with initially diagnosed axSpA prospectively underwent on 3.0 T MRI of sacroiliac joint (SIJ). The IVIM parameters (D, f, D*) were calculated using biexponential analysis. Ktrans, Kep, Ve, and Vp from DCE-MRI were obtained in SIJ. The uni-variable and multi-variable linear regression analyses were used to evaluate the correlation between the parameters from these two imaging methods after controlling confounders, such as bone marrow edema (BME), age, agenda, scopes, and localization of lesions, and course of the disease. Then, their correlations were measured by calculating the Pearson's correlation coefficient (r). Results The study eventually enrolled 234 patients (178 men, 56 women; mean age, 28.51 ± 9.50 years) with axSpA. With controlling confounders, D was independently related to Ktrans (regression coefficient [b] = 27.593, p < 0.001), Kep (b = −6.707, p = 0.021), and Ve (b = 131.074, p = 0.003), whereas f and D* had no independent correlation with the parameters from DCE MRI. The correlations above were exhibited with Pearson's correlation coefficients (r) (r = 0.662, −0.408, and 0.396, respectively, all p < 0.001). Conclusion There were independent correlations between D derived from IVIM DWI and Ktrans, Kep, and Ve derived from DCE-MRI. The factors which affect their correlations mainly included BME, gender, and scopes of lesions.